Mapping Potential Fishing Zones as Indicators of Pelagic Ecosystem Service Hotspots in the Makassar Strait using Satellite-Derived SST and Chlorophyll-a Anomalies - Ummu Salma; Fadil Apresia (CV. Science Tech Group, 2026)
This study developed an anomaly-based framework to map potential fishing zones (PFZs) in the Makassar Strait from satellite-derived sea surface temperature (SST) and chlorophyll-a (Chl-a) during 2022–2024. Daily GCOM-C/SGLI Level-3 Version 3 products were quality-masked, converted to physical units, aggregated to a 0.1° × 0.1° grid, and summarized as monthly composites. Monthly anomalies were then calculated relative to a month-specific three-year climatology. PFZs were defined as pixels simultaneously showing high Chl-a anomalies, represented by the 80th percentile of the spatial distribution of the temporal mean anomaly field, and relative cooling (SST anomaly ≤ 0). Monthly PFZ area ranged from 4,658 to 144,923 km², with a mean of 52,606 ± 33,834 km², whereas PFZ area fraction ranged from 0.012 to 0.352, with a mean of 0.130 ± 0.084. Seasonally, PFZs were most extensive during JJA (mean 66,973 km²; fraction 0.161) and least extensive during DJF (43,046 km²; fraction 0.112). Recurrent PFZ hotspots were concentrated in the central-southern Makassar Strait and along the eastern sector near the Sulawesi coast, where occurrence frequency reached about 58%. Valid-pixel diagnostics showed relatively stable AOI-level coverage (SST mean 0.534; Chl-a mean 0.548), indicating that the observed PFZ variability could not be explained by data gaps alone. These findings indicate that recurrent PFZs can be interpreted as pelagic ecosystem service hotspots that support ecosystem-based fisheries management, biodiversity conservation, and the sustainable use of marine resources, while aligning with SDG 14 (Life Below Water) and the post-2020 global biodiversity framework of the Convention on Biological Diversity.